2003
DOI: 10.1046/j.1365-2306.2003.01788.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutcracker oesophagus: a double‐blind, placebo‐controlled, cross‐over study of the effects of lansoprazole

Abstract: SUMMARYBackground: Nutcracker oesophagus is characterized by high-amplitude oesophageal contractions. Recent data have shown a high prevalence of gastro-oesophageal acid reflux in patients with nutcracker oesophagus and, in open-label trials, patients seemed to benefit from acid suppression. Therefore, it has been suggested that noncardiac chest pain in patients with nutcracker oesophagus may be related to reflux rather than to the motor abnormality itself. Aims: To investigate the effect of intensive acid-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
(28 reference statements)
2
16
2
3
Order By: Relevance
“…These multipeaked contractions occurred in a context of normal peristaltic amplitude and were converted to single peaked contractions after atropine injection. We also observed instances of Jackhammer Esophagus in GERD patients consistent with prior reports of hypercontractility in patients with reflux disease (4, 28). Relatively few patients in our series had pH monitoring studies done, but about 10% had reflux esophagitis on endoscopy and anti-reflux therapy was also associated with the resolution of symptoms in 8 of 15 patients and normalization of EPT studies in 1 of 2 cases who had follow-up studies.…”
Section: Discussionsupporting
confidence: 91%
“…These multipeaked contractions occurred in a context of normal peristaltic amplitude and were converted to single peaked contractions after atropine injection. We also observed instances of Jackhammer Esophagus in GERD patients consistent with prior reports of hypercontractility in patients with reflux disease (4, 28). Relatively few patients in our series had pH monitoring studies done, but about 10% had reflux esophagitis on endoscopy and anti-reflux therapy was also associated with the resolution of symptoms in 8 of 15 patients and normalization of EPT studies in 1 of 2 cases who had follow-up studies.…”
Section: Discussionsupporting
confidence: 91%
“…Uncontrolled surgical trials tend to show an improvement in reflux symptoms but no change in dysphagia or chest pain [18,20]. As a result, physicians commonly prescribe acid suppression therapy to such patients, although the results of the only randomized controlled trial of a proton pump inhibitor showed no benefit over placebo [21]. This is not inconsistent with our study in which only a minority found acid suppression helpful.…”
Section: Discussioncontrasting
confidence: 47%
“…Some authors observed an improvement in pain with antireflux therapy [37], while others did not obtain similar results [38]. In view of the retrospective nature of our study, we do not have additional information on this particular subject.…”
Section: Discussionmentioning
confidence: 65%